Interpreting EU Internal Market Powers in Light of Article 9 TFEU Social Objectives: Implications for the Attribution of Competences - Silvia Giudici (Croatian Yearbook of European Law and Policy)
The inclusion of the so-called ‘horizontal social clause’, namely Article 9 TFEU, in EU primary law imposes on the EU legislator an obligation to balance the objectives of a specific policy area with the social interests contained therein. For instance, when adopting internal market measures pursuant to Article 114 TFEU, the EU legislator would need to reconcile free trade aims and social interests. At the same time, this process also has consequences on the scope of EU competences. Hence, this article analyses which implications related to the scope of EU competences stem from the obligation to read Article 114 TFEU in light of Article 9 TFEU. In addition, it accounts for the consequences that this process entails for the division of powers between the EU and the Member States. The main argument proposed is that the obligation to read internal market powers in light of Article 9 TFEU not only influences the use of EU competences to pursue certain social objectives, but also leads to an expansion of EU harmonising powers in domains that remain of national competence. Thus, the division between EU and Member State competences becomes increasingly blurred. The Court of Justice of the EU has favoured this tendency by recognising on many occasions the possibility for the EU to rely on Article 114 TFEU, while developing a restrictive interpretation of the limitations of EU competences in social fields enshrined in the Treaties.